New “stars” of global economy: TICKS comes to replace BRICS - Iryna Chychkalo-Kondratska; Nataliya Bezrukova; Vitalii Svichkar (Journal of International Studies)
The paper discusses the reasons for the establishment of BRICS, and the role of the BRICS countries in the global economy today. Special attention is paid to the analysis of the factors, which caused the "destruction" of BRICS. The BRICS group is now being replaced by a new grouping of fast-growing economies – TICKS in which Russia and Brazil are replaced by Taiwan and South Korea. The authors analyzed the macroeconomic indicators of the TICKS countries and proposed a new structure of the grouping - Thailand, India, China, Korea, Singapore. These countries have fast-developing high-tech industries, increasing foreign investments and GDP, as it is proved here by the respective calculations of the authors.